Распределение корреляционного функционала при дискретном представлении сигналов НР - Мазманишвили, Александр Сергеевич; Рогожкин, Евгений Васильевич (НТУ "ХПИ", 2003)
Is it considered correlation functional, determined on complex-value normal Markov process. The expressions describing statistical properties such functional are receive
Keywords: ионосфера; ионосферная плазма